Can specialized surgical simulation influence resident career choice?. (December 2016) - Kaban, Jody M.; Dayama, Anand; Reddy, Srinivas H.; Teperman, Sheldon; Stone, Melvin E.
Abstract: Objective: Our institution began Advanced Trauma Operative Management (ATOM) simulation course in 2007 for senior residents with the aim of increasing opportunities for surgical trainees to gain operative trauma experience. The aim of our study was to evaluate the effect of the ATOM simulation course on residents' choice of trauma as a career as demonstrated by entrance into surgical critical care (SCC) fellowships. Design: Retrospective study of institutional data on graduating residents from 2002 to 2015. Residents were divided into pre-ATOM (2002–08) and post- (institution of) ATOM (2009–15) cohorts. The percentage of residents entering SCC fellowships was then compared among cohorts as well as to national trends. Results: Nationally the pre-ATOM group had 7057 graduating general surgery (GS) residents (847 SCC) and post-ATOM had 7581 graduating GS residents (1268 SCC). Locally the pre-ATOM group consisted of 40 graduating GS residents (1 SCC) and while the post-ATOM cohort had 51 graduating GS residents (9 SCC). The number of SCC fellows increased by 4.7% nationally and 15.7% institutionally between the two study groups. The increased interest in SCC was more than could be accounted for by national trends. Conclusions: Interest in a career in trauma was increased among residents graduating from this single institution after instituting ATOM as part of the educational curriculum. Highlights: A new trauma surgical simulation course was started. Resident interest in trauma increased after course implementation. Simulation may be a way to increase resident interest in needed specialties.